Pengembangan LKPD berbasis Problem Based Learning pada Materi Alkanol dan Alkoksi Alkana untuk Kelas XII SMA/MA - Riska Fitri Yeni; Suryelita Suryelita (Universitas Negeri Padang, 2023)
Alkanols and Alkoxy Alkanes are one of the material for carbon compounds studied in the even semester of grade XII SMA/MA. It studies the structures, nomenclatures, isomers, physical properties, chemical reactions, synthesis, uses, and the infrared spectrums. In the discussion, this material has interconnected orders. Problem-Based Learning Model is one of the learning models used to study this material. This research aims to develop a student worksheet based on Problem Based Learning on Alkanol and Alkoxy Alkane materials and to determine its validity category. This was a Research and Development (R&D) using the 4D development model consisting of four stages: define, design, develop and disseminate. This research was limited to the development stage. The research instrument was a validity questionnaire given to five expert validators. The validity data of the PBL-based student worksheet were analyzed by using the Aiken’s V formula scale. The analysis showed that the LKPD was very valid (0.86).